Structure And Meaning Of English Quotes Denoting Friendship (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
English quotes are an integral part of the language, which contributed to its success. They provide a means of expressing complex ideas and emotions in a concise and memorable way, making them useful for communication, inspiration, and reflection. Thanks to their unique features in semantic and structural aspects, English quotes denoting friendship can be a powerful tool for conveying the importance of friendship and the impact it can have on our lives. They can serve as a reminder to cherish our friends and cultivate strong, meaningful relationships. The aim of this study is to identify the syntactic fields in terms of structure and the semantic fields in terms of meaning in the English quotes denoting friendship and examine the frequency of these features. In the light of Quirk et al.'s theory of structure, the data of the study were collected, described, and analyzed under qualitative and quantitative approaches in order to discover the structure and meaning of English quotes denoting friendship. Among the 246 examples of EQDFs taken from the biggest quote site on the internet, namely: http://www.brainyquote.com, which was first published in 2001, is one of the oldest and most reliable quotation websites on the Internet. This thesis was carried out to point out and analyze these linguistic features with the hope of making a minor attribution to the teaching and learning of English quotes.